Digital Navigation and Fact-Checking Practices Among First-Time Voters: A Digital Ethnographic Study of Social Science Students in Bengkulu, Indonesia - Vinalti, Gushe; Jannah, Lizaida; Ayyun, Salju Qurrata; Kotyazhov, Andrey V. (Institut Agama Islam Negeri (IAIN) Manado, 2024)
The participation of first-time voters in Indonesia's 2024 General Election presents new challenges in the digital era, particularly regarding digital literacy to counter misinformation and hoaxes. This study aims to identify the digital literacy skills of students from the Faculty of Social and Political Sciences (FISIP), University of Bengkulu, in addressing political misinformation. Utilizing a digital ethnographic method with a qualitative approach, data were collected through in-depth interviews, observations, and document analysis involving eight first-time voters aged 17–19 years. The findings reveal that social media platforms such as Instagram, TikTok, and Twitter are the primary sources of political information, despite their vulnerability to hoaxes. Respondents demonstrated basic skills in identifying false information, such as fact-checking through applications and engaging in group discussions. However, they were also exposed to algorithmic echo chambers that amplify information biases. The study concludes that strong digital literacy skills can enhance responsible political participation. Strengthening digital literacy programs is essential to support the integrity of democracy.